Mauritius : Assessment Letter for the World Bank and African Development Bank. (Policy Papers; Policy Paper ;, 2009)
Mauritius has a long and sustained track record of implementing strong policies, and the authorities have responded appropriately to the global financial crisis by easing macroeconomic policies. While the crisis response has halted the decline in public debt, the public finances are fundamentally sound and external debt is sustainable. In light of the flexible exchange rate, the country's current reserve position is comfortable, and banks have remained liquid and profitable. With these strong economic fundamentals and an effective institutional policy framework, Mauritius is well placed to weather the current challenges.